Artificial Intelligence to Power the Future of Materials Science and Engineering. (21st April 2020) - Sha, Wuxin; Guo, Yaqing; Yuan, Qing; Tang, Shun; Zhang, Xinfang; Lu, Songfeng; Guo, Xin; Cao, Yuan-Cheng; Cheng, Shijie
Abstract : AI in Materials Science As reviewed by Prof. Yuan‐Cheng Cao and co‐workers in article number 1900143, with the assistance of machine learning, the application of AI in materials science including property prediction, synthesis route planning, and processing optimization, has been boosted. The future development direction is expounded from both hardware and software aspects to power the future of materials science and engineering.